Lebende Bilder Körperliche Nachahmung von Kunstwerken in der Goethezeit - Jooss, Birgit (Reimer Verlag, 1999)
Living pictures, tableaux vivants, are scenic arrangements of people who remain silent and motionless for a short time, thus forming an image for the viewer. The special practice of re-enacting works of art took its beginning in the Goethe period, which provides the temporal framework for this study. Birgit Jooss presents a multifaceted panorama of an art genre that has so far been mentioned only briefly in art and theater studies. A detailed, chronologically arranged catalog contains all sighted written sources on such events in which living pictures after works of arts were used.